Making a case for informal participation in occupational safety and health management - A. Baku, Anita; Tee, Keng Kok; Ab Rahman, Rozanah; Zawawi, Dahlia (Research Plus Journals, 2017)
A myriad of research have listed organisational commitment, reduced employee turnover, increased productivity amongst others, as some of the benefits of employee participation in management. Some studies on employee participation, however, indicates that, employees are generally reluctant to use formal avenues created for them to contribute to management. This is especially so because management mostly uses such formal avenues for a top-down information transfer. Also, employees have the fear of being victimised if they raise issues of concern that boarders on the use of finance or on something they assume may be offending to management during such meetings. In Ghana, the high annual accident and injury claims made by employees from the manufacturing industry requires urgent action by manufacturing organisations. Legislature on occupational safety and health (OSH) is scattered, with different over sight agencies, inadequate enforcement, and the absence of laws that require the establishment of a health and safety committee which is standard practice in most developed jurisdictions. In the light of the weak OSH legal and regulatory framework, coupled with the fact that employees feel reluctant to report their safety predicaments during formal meetings, it is important that management and employees create the necessary environment for employees to participate in safety management. Indeed, studies suggest that the existence of such informal avenues in organisations for employee participation in management decision making will enable open discussions on employee safety issues and therefore lead to the prioritisation of OSH in those organisations. Nevertheless, research indicates that informal participation has received little research attention especially with regards to Ghana. This study makes a case for the use of informal participation in ensuring safety in manufacturing companies in Ghana.